EXPLORING THE CONTENT AND STRUCTURE OF FUTURE PRIMARY SCHOOL TEACHERS’ EMOTIONAL INTELLIGENCE - Zadorozhna-Kniahnytska, Lenina; Khadzhinova, Irina; Netreba, Maryna; Voyevutko, Natalya; Poklad, Taisiia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of the present study is the theoretical justification and empirical research of the emotional intelligence level of students speciality "Primary Education", the disclosure of pedagogical conditions for the development of emotional intelligence of future primary school teachers in the process of their professional training in a higher education institution. The theoretical and experimental research was conducted during 2021-2023 on the basis of the Faculty of Psychology and Pedagogy of the Mariupol State University. It performed two main tasks: 1) determination of the emotional intelligence development level of future primary school teachers, in particular in the context of their professional training; 2) justification of effective pedagogical conditions for the development of emotional intelligence in future primary school teachers. The article describes the biological, social and pedagogical factors of the development of emotional intelligence. The principles of organizing the process of developing emotional intelligence in a higher education institution are considered: the principle of activity, contextuality, systematicity, and the principle of emotional variability. The analysis of empirical data obtained within the framework of the conducted research is given.